Supported TiO2/silica gel as an efficient and inexpensive catalyst for nonsolvent liquid‐phase oxidation of cyclohexylamine to cyclohexanone oxime. (10th November 2022) - Liu, Shuilin; Liu, Ning; Li, Aiyang; Wu, Suyun; Luo, Jianghuan; Tang, Xinde
Abstract: A benign approach is proposed for the highly efficient synthesis of cyclohexanone oxime through nonsolvent liquid‐phase oxidation of cyclohexylamine with dioxygen over supported TiO2 /silica gel. The as‐prepared catalyst was characterized by Brunauer–Emmett–Teller (BET), Fourier‐transform infrared spectroscopy (FT‐IR), scanning electron microscope (SEM), X‐ray photoelectron spectroscopy (XPS), and X‐ray powder diffraction (XRD) analyses. The results indicate that titanium active sites could be grafted on silica gel supports as catalytic centres. Various parameters such as reaction time and reaction temperature were systematically optimized; the results showed that supported 20%TiO2 /silica gel exhibited the best catalytic effect with 63.2% of amine conversion and 86.3% of selectivity to CHO. A possible pathway is proposed for cyclohexylamine oxidation over supported TiO2 /silica gel. The method developed in this study using dioxygen as the oxidant and inexpensive TiO2 /silica gel as an efficient catalyst has incredible industrial application potential for green synthesis of cyclohexanone oxime. Abstract : Probable reaction pathway of cyclohexylamine with dioxygen over supported TiO2 /silica gel.